Evidence of lipofuscin accumulation in the deep-water red shrimp Aristaeomorpha foliacea (Risso, 1827) - MEZZASALMA, V.; ZAGRA, M.; DI STEFANO, L.; RAGONESE, S.; BIANCHINI, M.L. (Mediterranean Marine Science, 2008)
Lipofuscin, a non-degradable, degenerative fluorescent pigment which accumulates in post-mitotic cells, represents a promising method for ageing marine crustaceans. The presence and accumulation of lipofuscin has been studied in the deep-water red shrimp Aristaeomorpha foliacea (Risso, 1827) to assess its use as a tool for ageing larger (i.e., older) specimens and thus improve knowledge of the growth and longevity of this species. Specimens, gathered during experimental trawl surveys carried out in the Strait of Sicily (Mediterranean Sea), were stored directly on-board in 10% buffered formaldehyde solution; their brain was thereafter removed, prepared with various current histological techniques and examined with a binocular microscope. Thin sections of the olfactory lobe cell mass were also analyzed using fluorescence microscopy, and the lipofuscin concentration was measured through image analysis. Various indices were computed for each individual by pooling data from many images: number and coverage of the lipofuscin granules per unit area, and mean individual area of the granules. Lipofuscin was detected in all specimens investigated with characteristics (grain typology and dimension) strictly resembling those already described in other crustacean species. The present preliminary results encourage further studies to develop and validate a methodology based on the use of lipofuscin for improving the relative ageing of large A. foliacea shrimps.